A reflection on the application of grounded theory in the exploration of the experiences of informal carers - J.D. Jeggels (AOSIS, 2009)
The aim of this paper is to reflect on the application of a qualitative research method that presents novice researchers with a variety of challenges. It is suggested that prospective users of the grounded theory method should seek guidance from experts in the field. However, to find these experts has proved to be quite challenging. The research topic lends itself to a qualitative study in general using the grounded theory method in particular. A qualitative approach was followed to describe the experiences of informal carers within their unique contexts. The guidelines of Strauss and Corbin (1990,1998) formed the basis for the development of the grounded theory. The challenges that will be described in a fair amount of detail in this paper include: an understanding of interpretive research paradigms, the philosophical underpinning of the method; its focus on social context; the inductive data analysis processes that allows for the emergence of a substantive theory from empirical data. Prospective scholars should also recognize that grounded theorists follow different approaches to the application of the method. Some subscribe to the traditions of the founders (Glaser & Strauss, 1967), while others choose the analytical rules and procedures proposed by the followers of the method (Strauss & Corbin, 1990,1998). In this paper I reflect on the application of the grounded theory method to explore the experiences of informal carers during the transition of the elderly from hospital to home. The research outcomes showed that informal carers were facilitating care during the transition of the elderly from hospital to home by revealing the link between facilitating care, the basic social process, and other categories associated with informal health care. These categories include: the prior relationship between the carer and the elderly, the traumatic incident, the need for role fitting, maintenance- and repair care, as well as, the consequences of facilitating care, i.e. connected or disconnected care. It is recommended that informal carers be recognized as essential community assets and that they are included in the health care system of the country; that they need information as well as financial and material resources and that they require the support of family, home-based workers and professionals alike.